Multiwalled carbon nanotube pretreatment to enhance tensile properties, process stability, and filler dispersion of polyamide 66 nanocomposites. (1st October 2020) - Kang, Seonku; Kim, Jongwon; Park, Jong Hyuk; Jung, Inhwa; Park, Min
Abstract: Multiwalled carbon nanotube-dispersed polyamide 66 nanocomposites (PA66/MWCNTs) were fabricated by melt-mixing pretreated MWCNTs and PA66, and the effects of pretreating techniques and types of pretreating materials were investigated. The non-fluffy method (NFM) and the dry-coating method (DCM) were studied to determine the effects of pretreatment techniques. The tensile properties were enhanced by the NFM. However, the DCM improved the stability of the process, which greatly decreased the coefficient of variation (CV) of the physical properties. To examine the effects of pretreatment materials, an epoxy modifier (bisphenol-F diglycidyl ether; DGEBF), a fluorosurfactant (FSO100), and a silane coupling agent ((3-aminopropyl)triethoxysilane; APTES) were evaluated. Compared with DGEBF, FSO100 and APTES noticeably improved the tensile properties. However, DGEBF provided highly stable physical properties. Furthermore, the relationship between the stability of physical properties and MWCNT dispersion was investigated. Dispersion was quantified in terms of the dispersion ratio, which was determined by Voronoi diagram analysis. The dispersion ratio was inversely correlated with the CVs of the physical properties. Highlights: The effects of various pretreatments on multiwalled carbon nanotube (MWCNTs) dispersed polyamide 66 (PA66) nanocomposites (PA66/MWCNTs) were investigated. The non-fluffy method (NFM) was developed based on planetary centrifugal mixing (PCM) and the dry-coating method (DCM) based on Henschel mixing (HM) was applied for pretreatment of MWCNTs. As pretreatment materials, the effects of an epoxy modifier (bisphenol-F diglycidyl ether; DGEBF), a fluorosurfactant (FSO100), and a silane coupling agent ((3-aminopropyl)triethoxysilane; APTES) were investigated. To quantify the dispersion of MWCNTs in PA66, dispersion ratios were obtained through a Voronoi diagram analysis, and their correlation with the mechanical properties and the coefficient of variation (CV) were investigated. The dispersion ratio was inversely correlated with the CV of a physical property, which can be an indicator of the process stability.